Mass Transfer Phenomena in Rotating Corrugated Photocatalytic Reactors - Xiang, Yuanyuan (Université d'Ottawa / University of Ottawa, 2014)
Photocatalysis is a green technology that has been widely used in wastewater treatment. In this work, mass transfer processes in corrugated photocatalytic reactors were characterized both experimentally and through computer simulations. For the experimental work, various drum rotational speeds, reactor liquid volumes and number of corrugations were studied to elucidate their effects on mass transfer phenomena. The mass transfer rate was found to increase with increasing rotational speed. Liquid volumes in the reactor significantly affect the mass transfer rate when 20% of the surface area of the drum was immersed. A higher mass transfer rate was found using the drum with 28 corrugations, which had the lowest mass transfer coefficient when compared to the drums with 13 and 16 corrugations. In the computer simulations, velocity and concentration fields within the corrugated reactors were modelled to explore the characteristics of mass transfer processes. The mass transfer coefficients predicted by the simulations were lower than those measured experimentally due to mass transfer limitations occurring between the corrugation volume and bulk solution in the simulations. Based on mass transfer characteristics, it was determined that the drum with 28 corrugations was the most efficient photocatalytic reactor, and had the lowest mass transfer coefficient among those studied.
Keywords: mass transfer; corrugated drum; photoreactor; simulation; CFD